A construção dos deuses no de natura deorum de Marco Tulio Cícero - Rabelo, Sara Gonçalves (2017)
This dissertation aims to present and discuss the epicurean, stoic and new academy doctrines with the aim of understanding the construction of the gods in the De Natura Deorum by Marco Tulio Cicero. For this work it was not made a history of general, therefore the external elements were not deepened, but it was made a history of the philosophy of Cicero in order to understand the conceptions of the author. The Ciceronian work is a philosophical dialogue written in 45 BC by Marcus Tullius Cicero which was organized in three books and in each of them is discussed the Epicurean, Stoic and New Academy doctrines. Many currents of thought that are used by the author present an attempt to demonstrate that there are many connections and divergences between them. In this work, Cicero uses a clever dialectical style of confrontation of ideas to ensure that each doctrine exposes its philosophy while being confronted by those who are listening to the discussion. Each doctrine exposed is represented by a character: Caio Veleio is the epicurean, Lucílio Balbo is the stoic and Cota is the academic. Considerations were made about the period that the book was written, the Hellenistic, as well as an analysis of Cicero's life, which is essential to understand why, almost at the end of his life, he decided to write about the existence of the gods. In addition, a brief analysis of the doctrines was made based on studies done by other authors, which contributes to understand what remains of Cicero after the Hellenistic doctrines. As it will be possible to see in the conclusion, Cicero is not an effective participant of the dialogue, but his conceptions appear in the voice of the academic Balbo, who is responsible for refuting all the exposed conceptions on the gods.